DESIGN THINKING: AN ANALYSIS IN BUSINESS EDUCATION - Hayati, Neneung Ratna; Ependi, Maolana; Putra, Ryan Andriana; Wildan, MD. (Komitmen: Jurnal Ilmiah Manajemen, 2024)
Design Thinking is not only a tool applied to foster innovation in business, it is also a new and prominent approach in education. Being a creative process that enables academics to meet the needs of the world of work and to produce innovative individuals, it is emerging as a contemporary pedagogical tool, which can be used at all levels of education with later career implications. Despite its growing importance, the application of Design Thinking into business education has been slow and partial, even though business education is currently in crisis as traditional pedagogical tools are unable to produce individuals capable of facing the challenges of the 21st century.st This study explores current trends in applying Design Thinking into higher education, with a particular focus on the strategies of leading schools. Using a case study approach, we provide a road map in the business strategies of educational institutions, and in particular for business schools, that seek to integrate this new tool into their curriculum.